Minimum diet diversity-women score and predictors of school adolescent girl stunting and thinness in Northwest Ethiopia - Yajeb Melesse; Zeweter Abebe (BMC Public Health)
Abstract Background Limited data exist on adolescent nutrition. This school-based cross-sectional study aimed to assess dietary practices, nutritional status, and associated factors among adolescent girls. Methods Two hundred seventy-nine primary and secondary school girls were selected via multistage sampling. A pretested questionnaire and 24-h recall method were employed to gather data on background characteristics and dietary practices. The questionnaire was pretested with 20 adolescents from nonparticipating schools to assess clarity and reliability. Feedback from the pretest was used to refine the questionnaire. The minimum dietary diversity for women (MDD-W) was used as an indicator of diet quality, where women were considered to have adequate dietary diversity if they consumed at least five of ten food groups in the past 24 h. Key informant interviews were used to explore nutritional problems, while anthropometric measurements were taken to assess nutritional status. Height and weight, combined with age, were used to calculate height-for-age and BMI-for-age z scores via WHO AnthroPlus software. Nutritional status was categorized as stunted (< -2SD), thin (< -2SD), normal (-2SD to + 2SD), or overweight (> + 2SD). A multivariate binary logistic regression model identified predictors of nutritional status. The quantitative data were analyzed via SPSS, and the qualitative data were analyzed via ATLAS.ti. Results Only 24% of the students met the MDD-W. Predominant consumption of plant-source foods (100%) and low animal-source food intake (< 20%) were observed. Environmental, social, and cultural factors are barriers to nutrition, whereas cultural food preferences act as reinforcing factors. The prevalence rates of thinness, stunting, and overweight were 7.2%, 6.4%, and 5.7%, respectively, with undernutrition being more prevalent in younger adolescents (10–14 years). Adolescents with low fast food consumption and those in late adolescence were less likely to be stunted or thin. Conclusion Poor dietary practices and undernutrition, particularly among younger adolescents, were observed. Comprehensive programs addressing environmental, social, and cultural barriers are needed to improve adolescent nutrition.